Population Genomic Sequencing Delineates Global Landscape of Copy Number Variations that Drive Domestication and Breed Formation of in Chicken - Chen, Xia; Bai, Xue; Liu, Huagui; Zhao, Binbin; Yan, Zhixun; Hou, Yali; Chu, Qin (Frontiers in Genetics, 2022)
Copy number variation (CNV) is an important genetic mechanism that drives evolution and generates new phenotypic variations. To explore the impact of CNV on chicken domestication and breed shaping, the whole-genome CNVs were detected via multiple methods. Using the whole-genome sequencing data from 51 individuals, corresponding to six domestic breeds and wild red jungle fowl (RJF), we determined 19,329 duplications and 98,736 deletions, which covered 11,123 copy number variation regions (CNVRs) and 2,636 protein-coding genes. The principal component analysis (PCA) showed that these individuals could be divided into four populations according to their domestication and selection purpose. Seventy-two highly duplicated CNVRs were detected across all individuals, revealing pivotal roles of nervous system (NRG3, NCAM2), sensory (OR), and follicle development (VTG2) in chicken genome. When contrasting the CNVs of domestic breeds to those of RJFs, 235 CNVRs harboring 255 protein-coding genes, which were predominantly involved in pathways of nervous, immunity, and reproductive system development, were discovered. In breed-specific CNVRs, some valuable genes were identified, including HOXB7 for beard trait in Beijing You chicken; EDN3, SLMO2, TUBB1, and GFPT1 for melanin deposition in Silkie chicken; and SORCS2 for aggressiveness in Luxi Game fowl. Moreover, CSMD1 and NTRK3 with high duplications found exclusively in White Leghorn chicken, and POLR3H, MCM9, DOCK3, and AKR1B1L found in Recessive White Rock chicken may contribute to high egg production and fast-growing traits, respectively. The candidate genes of breed characteristics are valuable resources for further studies on phenotypic variation and the artificial breeding of chickens.